Ripples Have Distinct Spectral Properties and Phase-Amplitude Coupling With Slow Waves, but Indistinct Unit Firing, in Human Epileptogenic Hippocampus - Weiss, Shennan A.; Song, Inkyung; Leng, Mei; Pastore, Tomás; Slezak, Diego; Waldman, Zachary; Orosz, Iren; Gorniak, Richard; Donmez, Mustafa; Sharan, Ashwini; Wu, Chengyuan; Fried, Itzhak; et al. (Frontiers in Neurology, 2020)
Ripple oscillations in the normal hippocampus are involved in memory consolidation during rest and sleep. In the epileptic brain, increased ripple and fast ripple (200-600 Hz) rates serve as a biomarker of epileptogenic brain. We report that both ripples and fast ripples exhibit a preferred phase angle of coupling with the trough-peak (On-Off state transition) of the sleep slow wave in the hippocampal seizure onset zone (SOZ). Ripples on slow waves in the hippocampal SOZ also had a lower power, greater spectral frequency, and shorter duration than those in the non-SOZ. We found that slow waves in the mesial temporal lobe modulated the baseline firing rate of excitatory neurons, but did not significantly influence the increased firing rate associated with ripples. In summary, pathological ripples and fast ripples occur preferentially during the On-Off state transition in the epileptogenic hippocampus, but ripples do not require the increased recruitment of excitatory neurons.